Adapting TFMCC Protocol in PIM-DM for avoiding Congestion Control in Wired Multicast - Deepa, V B; Ushadevi, M B (International Journal of Computer Sciences and Engineering, 2018)
PIM-DM is a multicast routing protocol that uses the underlying unicast routing information base to flood multicast datagrams to all multicast routers. End-to-End Multicast Congestion Control (MCC) is a complex problem. TFMCC (TCP Friendly Multicast Congestion Control) is a congestion control mechanism for multicast transmissions. Where the sending rate is adapted to the receiver experiencing the worst network conditions TFMCC shows better performance. TFMCC is stable and responsive under a wide range of network conditions and scales to receiver sets on the order of several thousand receivers. In this paper, we implemented TFMCC protocol to PIM-DM model and also we compare TFMCC with TCP behaviour. TFMCC is designed to be reasonably fair when competing for bandwidth, sending rate, varying number of links, different receiver capacity and scalability. Experimental results show tremendous performance improvement in throughput without affecting the TCP fairness of the protocol.